The role of job crafting in mediating the relationship between conscientiousness and job performance: Insights from knowledge workers in the FMCG industry - Bella, Catharine; Suyasa, P Tommy Y. Sumatera; Tumanggor, Raja Oloan (Jurnal Psikologi, 2024)
Background: The development of Fast-Moving Consumer Goods (FMCG) resents challenges in enhancing job performance. While personality traits, particularly conscientiousness, are known to directly influence job performance, there is limited understanding of how job crafting behavior contributes to this relationship.Purpose: This research investigates the role of job crafting (task crafting,elational crafting, & cognitive crafting) in mediating the relationship between conscientiousness and job performance (task & contextual performance).Method: Quantitative research was conducted with 185 participants who are knowledge workers in a Fast-Moving Consumer Goods (FMCG) company with an average of 29.67 years old (SD = 4.50), with a minimumof 1 year of tenure. Data analysis using Confirmatory Factor Analysis (CFA) and linear regression. Findings: Results indicated that task crafting, relational crafting, and cognitive crafting worked as a partial mediator in the relationship between conscientiousness and task performance. Meanwhile, the relationship between conscientiousness and contextual performance was insignificant, indicating the need of further study regarding work engagement and job characteristics of FMCG employees. Implication: The result encouraged organizations to support job crafting by providing training and facilitating job modification.